Salmonella Enteritidis Effector AvrA Suppresses Autophagy by Reducing Beclin-1 Protein - Jiao, Yang; Zhang, Yong-guo; Lin, Zhijie; Lu, Rong; Xia, Yinglin; Meng, Chuang; Pan, Zhimin; Xu, Xiulong; Jiao, Xinan; Sun, Jun (Frontiers in Immunology, 2020)
Autophagy is a cellular process to clear pathogens. Salmonella enterica serovar Enteritidis (S.E) has emerged as one of the most important food-borne pathogens. However, major studies still focus on Salmonella enterica serovar Typhimurium. Here, we reported that AvrA, a S. Enteritidis effector, inhibited autophagy to promote bacterial survival in the host. We found that AvrA regulates the conversion of LC3 I into LC3 II and the enrichment of lysosomes. Beclin-1, a key molecular regulator of autophagy, was decreased after AvrA expressed strain colonization. In S.E-AvrA--infected cells, we found the increases of protein levels of p-JNK and p-c-Jun and the transcription level of AP-1. AvrA-reduction of Beclin-1 protein expression is through the JNK pathway. The JNK inhibitor abolished the AvrA-reduced Beclin-1 protein expression. Moreover, we identified that the AvrA mutation C186A abolished its regulation of Beclin-1 expression. In addition, AvrA protein was found interacted with Beclin-1. In organoids and infected mice, we explored the physiologically related effects and mechanism of AvrA in reducing Beclin-1 through the JNK pathway, thus attenuating autophagic responses. This finding not only indicates an important role of S. Enteritidis effector in reducing host protein as a strategy to suppress autophagy, but also suggests manipulating autophagy as a new strategy to treat infectious diseases.